2015
DOI: 10.1080/10810730.2015.1080331
|View full text |Cite
|
Sign up to set email alerts
|

Medication Nonadherence Before Hospitalization for Acute Cardiac Events

Abstract: Background Medication non-adherence increases the risk of hospitalization and poor outcomes, particularly among patients with cardiovascular disease (CVD). Purpose To examine characteristics associated with medication non-adherence among adults hospitalized for CVD. Methods Patients in the Vanderbilt Inpatient Cohort Study who were admitted for acute coronary syndromes or heart failure completed validated assessments of self-reported medication adherence (the Adherence to Refills and Medications Scale [ARM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 57 publications
0
37
3
4
Order By: Relevance
“…Low health literacy even though has been previously found to be a mediator of adverse outcomes 44 and of self-reported adherence 39 was not significant in multivariate models that used a categorical objective measure of adherence. This may suggest a confounding effect with the other factors or lack of discriminatory ability when using a dichotomized MPR, since the health literacy effect was significant when the continuous MPR measure was used.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Low health literacy even though has been previously found to be a mediator of adverse outcomes 44 and of self-reported adherence 39 was not significant in multivariate models that used a categorical objective measure of adherence. This may suggest a confounding effect with the other factors or lack of discriminatory ability when using a dichotomized MPR, since the health literacy effect was significant when the continuous MPR measure was used.…”
Section: Discussionmentioning
confidence: 64%
“…However, the literature has been mixed regarding the association between adherence to medications and depressive symptoms and it seems to vary according to disease state. Nevertheless, depression has been a consistent predictor of adherence among diabetic patients 33 and more recently among subjects hospitalized with acute cardiac events 39 .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] We also found that adults who had a usual source of care, were married, and had higher education had greater odds of statin use, which is consistent with prior research. [37][38][39][40] Understanding barriers to statin use-including patient, clinician, and delivery system factors as well as costs-is important when identifying strategies to improve quality of care. Statins are now available to many Americans at little-to-no out-ofpocket cost regardless of whether they are being used for primary or secondary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oral health, self‐efficacy is related to a range of other general health behaviours and measures. Perceived health competence has been associated with physical activity among cancer patients , and health competence has been related to medication non‐adherence among adults hospitalized for cardiovascular disease . Perceived health competence and social support have been reported to buffer the negative effects of post‐discharge stress that may occur following hospitalization for cardiac disease .…”
Section: Discussionmentioning
confidence: 99%